Neformalni oskrbovalci - Svetelšek, Ajda (Kakovostna starost, 2018)
The article is presenting the data of two studies about informal carers in Slovenia. It compares the characteristics of informal carers from representative Slovenian sample and from informal carers, who participated in the trainings for informal care at Anton Trstenjak Institute of Genrontology and Integrational Relations. The comparison of demographic and some other characteristics of the two samples of informal carers aims at strengthening the identity of informal carers and some of the problems they are faced with when doing their work, which is often overlooked, but very important. Findings of present study are bringing new insights into motivation of carers for improving the care they are providing and for strenghtening their own health.
Keywords: dolgotrajna oskrba; družinski oskrbovalci; neformalni oskrbovalci; usposabljanje